Prodrugs of Thyrotropin-Releasing Hormone and Related Peptides as Central Nervous System Agents - Laszlo Prokai (Molecules, 2009)
Prodrug design for brain delivery of small- and medium-sized neuropeptides was reviewed, focusing on thyrotropin-releasing hormone and structurally related peptides as examples. We have summarized our most important advances in methodology, as well as assessed the benefits and limitations of bioreversible chemical manipulation techniques to achieve targeting of the parent molecules into the central nervous system. The value of prodrug-amenable analogues as potential drug-like central nervous systems agents was highlighted.